Penanaman Akhlakul Karimah Melalui Filosofi Merdeka Belajar Siswa Sekolah Dasar - Hasanah, Intan Andriani; Faisal, Faisal; Ihwanah, Al (Limas PGMI, 2023)
This research aims 1) To determine the cultivation of morals in class V students at SDIT Al Furqon Palembang. 2) To find out the approach to the philosophy of independent learning for class V students at SDIT Al Furqon Palembang. 3) To find out the factors that influence the cultivation of morals through an independent learning philosophy approach for class V students at SDIT Al Furqon Palembang. The data collection techniques are through observation, interviews and documentation. The results of this research show that 1) There is a school program that aims to instill good morals, namely PPA (Week for Cultivating Adab). 2) In implementing independent learning activities, the school has implemented them well. The independent learning program that supports the cultivation of morals is the P5 activity. 3) The supporting factors are a. teachers, b. parents, c. facilities, d. human resources. While the inhibiting factors are; a. consistency of activities, b. external environment, c. mindset or thought patterns.